DETERMINATION OF THE THERMODYNAMIC FUNCTIONS OF THE POLYMORPHIC TRANSITION OF THE Cu8Si0.5Ge0.5S6 ARGYRODITE PHASE BY DSC METHOD - Khanmamedov Ilham Nazim; Bayramva Ulviyya Rafiq; Mashadiyeva Leyla Farkhad (Research Retrieval and Academic Letters, 2023)
Complex chalcogenides based on copper and silver are promising functional materials [1-5]. In particular, compounds of the argyrodite family with the general formula A8BIVX6 (where A-Cu, Ag; BIV-Si, Ge, Sn; X-S, Se, Te) have a number of valuable functional properties and are the object of study by many research groups. These compounds are attracting more and more attention as promising candidates for thermoelectric materials due to their excellent transport properties and relatively low thermal conductivity and, along with this, low toxicity, as well as the wide distribution of constituent components [6-10]. Most of these compounds have phase transitions at relatively low temperatures (310–520 K). As a rule, high-temperature modifications crystallize in a cubic structure, while low-temperature phases have a lower symmetry. Most of the high-temperature phases of these compounds, due to the peculiarities of the crystal structure, have a mixed electronic-ionic conductivity due to the high mobility of copper (or silver) ions. The thermodynamic properties of the phase transitions of these compounds have not been studied.